2014
DOI: 10.1002/jnr.23398
|View full text |Cite
|
Sign up to set email alerts
|

Critical neuroprotective roles of heme oxygenase‐1 induction against axonal injury‐induced retinal ganglion cell death

Abstract: Although axonal damage induces significant retinal ganglion cell (RGC) death, small numbers of RGCs are able to survive up to 7 days after optic nerve crush (NC) injury. To develop new treatments, we set out to identify patterns of change in the gene expression of axonal damage-resistant RGCs. To compensate for the low density of RGCs in the retina, we performed retrograde labeling of these cells with 4Di-10ASP in adult mice and 7 days after NC purified the RGCs with fluorescence-activated cell sorting. Gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…Our study with C57BL/6J mice found an average RGC density of 3,119 ± 397 cells/mm 2 (mean ± SD), yielding a coefficient of variation of 12.7%. This is similar to results from other studies assessing density across large areas of the retina – which have likewise given rise to coefficients of variation between 8.9% and 13.7% in various inbred mouse strains (Salinas-Navarro, Jimenez-Lopez et al 2009, Galindo-Romero, Aviles-Trigueros et al 2011, Germain, Istillarte et al 2013, Himori, Maruyama et al 2014). With this degree of natural variability present, even among completely inbred mice with retinas free of overt disease, quantifications using greater sampling coverage are a prudent measure to avoid spurious results.…”
Section: Discussionsupporting
confidence: 89%
“…Our study with C57BL/6J mice found an average RGC density of 3,119 ± 397 cells/mm 2 (mean ± SD), yielding a coefficient of variation of 12.7%. This is similar to results from other studies assessing density across large areas of the retina – which have likewise given rise to coefficients of variation between 8.9% and 13.7% in various inbred mouse strains (Salinas-Navarro, Jimenez-Lopez et al 2009, Galindo-Romero, Aviles-Trigueros et al 2011, Germain, Istillarte et al 2013, Himori, Maruyama et al 2014). With this degree of natural variability present, even among completely inbred mice with retinas free of overt disease, quantifications using greater sampling coverage are a prudent measure to avoid spurious results.…”
Section: Discussionsupporting
confidence: 89%
“…55,56 Moreover, because Atf3, Lcn2, and Tnfrsf12a upregulation after ONC had been found in isolated retrograde labeling RGCs by FACS 41 whose purity reaches up to 96%. 41,57,58 RGCs are thought to be a predominant source of these molecules. Further evaluations using specific markers for each cell type are needed.…”
Section: Discussionmentioning
confidence: 99%
“…; Himori et al. ). The magnitude of HO‐1 induction therefore might be important in the defence of organisms against oxidative stress‐mediated injuries and other diverse factors (Amersi et al.…”
Section: Discussionmentioning
confidence: 96%